Signal and Noise Separation From Satellite Magnetic Field Data Through Independent Component Analysis: Prospect of Magnetic Measurements Without Boom and Noise Source Information. Issue 5 (10th May 2021) - Imajo, S.; Nosé, M.; Aida, M.; Matsumoto, H.; Higashio, N.; Tokunaga, T.; Matsuoka, A.
Abstract: We propose an application of the independent component analysis (ICA) to separate satellite‐induced time‐varying stray fields from magnetic field data obtained using onboard multiple magnetometers. The ICA is a method for estimating source signals at multiple sites so that the estimated source signals can become statistically independent of each other. Since stray field variations are statistically independent of external natural field variations, the ICA method is expected to separate the natural variations from stray fields. Thus, we applied the ICA to magnetic field data from the first Quasi‐Zenith Satellite, which has two triaxial fluxgate magnetometers, without using an extendable boom. First, we removed the long‐period trend from the original data to create detrended data. Then, we applied the FastICA algorithm to the detrended data and obtained six independent components (ICs). The stray fields were successfully separated into three ICs (noise ICs), and the natural signals were represented by the other three ICs (signal ICs). Finally, we restored the observed signals from the signal ICs, and confirmed that the natural phenomena variations were not altered by the processing step. We also proposed a selection method of the noise ICs using the C coefficient, which is the coefficient of the variance of the mixing vectors. There was a large difference in C between the ICs whose C coefficients are the largest third and fourth ones. Overall, these results demonstrate the possibility that the ICA method can support for boom‐less magnetic observations in future satellite missions. Plain Language Summary: To obtain magnetic field data for space science, reducing the stray fields from satellite electronics is required. A usual method for reducing stray fields is the placement of the magnetic sensors away from a satellite's body using long booms. However, it is difficult to use such booms for some satellites due to operational restrictions and financial costs. Thus, we propose a new method using the independent component analysis (ICA) without booms or any prior information regarding the sources of stray fields. The proposed method is based on the reasonable assumptions that stray field variations are statistically independent of natural magnetic variations, and that observed magnetic fields are a mixture of them. In this study, in particular, we applied the ICA method to the magnetic field data from the first Quasi‐Zenith Satellite, which has two magnetic sensors, without using booms. Although the original data were heavily obscured by the three kinds of major stray fields, the noise independent components and signal independent components were successfully separated. The noise‐cleaned data show fewer stray fields without any alterations of natural variations. Overall, these results demonstrate the possibility that the ICA method can provide more opportunities for adding magnetic field observations to future satellites. Key Points: We propose an application of the independent component analysis (ICA) for signal and noise separation from satellite magnetic field data We successfully separated time‐varying stray fields from magnetic field data measured by two magnetometers onboard of QZS‐1 without booms The proposed ICA method can give more opportunities for loading magnetometers in future satellites